Digitalization of the Public Procurement System in Indonesia: Challenges and Problems - Rizky Amalia; Muhammad Amirul Alfan; Maghfirah Aliefia; Mohd Sharil Nizam bin Md Radzi; Faizal Kurniawan (Universitas Airlangga, 2023)
The Indonesian government carries out goods/services procurement activities in the framework of the welfare of its people. From time to time the procurement of goods/services has developed and, in the current digital era, it has begun to switch to electronic-based procurement. To answer the challenges of these developments, as well as to prevent fraud or violations of the law, a solid system is needed that can accommodate all of this. The blockchain concept can be an alternative to answer this issue because the blockchain system has advantages in terms of security and transparency. The research method used in this article is legal research with a statute and conceptual approach. The purpose of this article is to become a reference regarding the probability of using the blockchain system in the law of procurement of goods and services in Indonesia. The findings of this study are that no country has yet implemented a blockchain system for the procurement of goods/services. Blockchain technology has been implemented by the private sector, namely by Walmart, Nestle, and Unilever who use blockchain technology as the basis of their supply chain management which, with this system, can increase effectiveness and efficiency as well as afford a good level of security. Thus the blockchain system for procuring goods/services in Indonesia can be a method that can be applied to increase efficiency and aspects of transparency to reduce misuse in the procurement of goods/services.